Design and performance analysis of advanced optical communications system utilizing optical frequency comb generation - Al-janabi, Atheer Adnan Salman (My University, 2023)
Bu tezde, Optisystem yazılımı aracılığıyla 40 GHz dalga boyu bölmeli çoğullama iletişim sistemi tabanlı optik frekans tarama üreteci (WDM–OFCG) tasarlanmış ve incelenmiştir. Önerilen tasarım, 40 GHz sabit kanal aralığı ve -10.84 dBm ortalama güç ile 25 adede kadar kanal üretmiştir. Üretilen tarak, 1546.17 nm ile 1553.85 nm arasında değişen yaklaşık 8 nm'ye yayılır. Ek olarak, elde edilen performansı değerlendirmek için üretilen tarak, WDM fiber optik sisteminde 120 km bağlantı mesafesi üzerinden 375 Gbps bit hızında bir taşıyıcı olarak kullanılır; bu, yaklaşık 45000 (Gbps.km) bit hızlı ürün tekrarlayıcı mesafesini temsil eder. Önerilen OFCG'de giriş optik gücü, 1550 nm dalga boyunda sürekli bir lazer kaynağından (CW) elde edilir. Ek olarak, sinüs sinyalini iki yola ayırmak için bir çatala bir sinüs üreteci bağlanır, her iki sinyal de iki elektrik amplifikatörü tarafından yükseltilir ve MZM'ye bağlanır. Oluşturulan tarak, her kanalı tek başına çıkarmak için bir WDM çoğullamaya (WDM) bağlanır. Ardından, her bir kanal bir Mach-Zehnder Modülatör MZM aracılığıyla kiplenir ve tüm modüle edilmiş kanalları tek modlu fiber (SMF) yoluyla göndermek için bir WDM aracılığıyla birleştirir. Ayrıca, renk dağılımını 0.4 dB.km'lik zayıflama kayıpları içinde telafi etmek için bir dağılım dengeleme fiberi (DCF) kullanılır. DCF'den önce/ sonra optik sinyali yükseltmek için iki optik amplifikatör kullanıldı. Son olarak, alma sinyali, alıcı düzeneği kullanılarak bit hata oranı BER ve kalite Q-Factor açısından değerlendirilir.

In this dissertation, we use the Opti system program to develop and analyze a wavelength division multiplexing optical frequency comb generator (WDM-OFCG) for a 40 GHz WDM communication system. Maximum output power of -10.84 dBm and a constant channel spacing of 40 GHz were achieved by the proposed architecture. The comb that is produced has a wavelength range of 1546.17 nm to 1553.85 nm, or roughly 8 nm. To further assess the results, the created comb is used as a carrier at a bit rate of 375 Gbps over a link distance of 120 km within a WDM fiber optic system. This is equivalent to roughly 45,000 (Gbps.km) of bit rate product repeater distance. The proposed OFCG relies on an input optical power from a single continuous wave (CW) laser source operating at 1550 nm in wavelength. Additionally, two electrical amplifiers are used to boost the strength of the sine signal before it is sent to Mach-Zehnder Modulators (MZM). The sine signal is generated by connecting a sine generator to a fork. In order to separate each channel, the resulting comb is wired into a WDM multiplexing WDM. After that, we use MZMs to modulate each individual channel before combining them in WDM for transmission across a single mode fiber (SMF). In addition, chromatic dispersion within attenuation losses of 0.4 dB.km is compensated by employing a dispersion compensation fiber (DCF). The optical signal was amplified both before and after the DCF by use of two separate optical amplifiers. Finally, the receiver module's output signal is analyzed for its bit error rate (BER) and quality Q-Factor.
Keywords: and opitacl comb generation; and opitacl comb generation Electric; comunication; Electric; Electric engineering; Elektrik mühendisliği; Optisystem